DHAMMONG : A RAIN RITUAL IN MADURA (A STUDY ON ITS HISTORY, FUNCTION, AND HISTOR ORY SIMBOLIC MEANING) - Nor Hasan; Edi Susanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2020)
This article attempted to trace the existence of Dhâmmong tradition in the following scopes, namely: (1) Madurese perception against Dhâmmong , (2) the function and symbolic meaning of Dhâmmong in human life, and (3) the efforts of the Madurese community to preserve the Dhâmmong tradition. Through a descriptive phenomenological analysis, this study revealed that Dhâmmong is a hereditary tradition carried out by the Madurese community, it is urged by the community’s anxiety caused by the long dry season (némor lanjheng). Dhâmmong functionsas a means for salametan, paying respect for the ancestors, strengthening human relations (silaturrahim ), Bhek Rembhek, and nguri berkah (the fertility of the earth). The offerings and mouth-music by imitating the sounds of animals represent a strong desire and wishof the community for the immediate rainfall that could pour out blessings for the community. Hence, the community’s efforts to preserve Dhâmmong are: (1) introducing and involving the younger generation in the ritual, and (2) setting and changing the time sequence of Dhâmmong implementation from night to daytime.